Inflammation in multiple system atrophy - Leńska-Mieciek, Marta; Madetko-Alster, Natalia; Alster, Piotr; Królicki, Leszek; Fiszer, Urszula; Koziorowski, Dariusz (Frontiers in Immunology, 2023)
Misfolding protein aggregation inside or outside cells is the major pathological hallmark of several neurodegenerative diseases. Among proteinopathies are neurodegenerative diseases with atypical parkinsonism and an accumulation of insoluble fibrillary alfa-synuclein (synucleinopathies) or hyperphosphorylated tau protein fragments (tauopathies). As there are no available therapies to slow or halt the progression of those diseases, thus targeting the inflammatory process is promising. The inflammatory biomarkers could also help in the differential diagnosis of parkinsonian syndromes. Here, we review inflammation’s role in multiple systems atrophy pathogenesis, diagnosis and treatment.